Benjamin's Ground - Rainer Nägele (Studies in 20th & 21st Century Literature, 1986)
Benjamin‘s reading of Hölderlin in one of his earliest essays already delineates some of the major constellations of his thought. Searching for the ground of language and of poetic language in particular, Benjamin sets out to lay the ground for the possibility of literary criticism. His text enters into a specific relationship with Hölderlin's theory of poetics and poetic language. The movement of this search leads through a metaphoric relationship of "surface" and "depth" toward an ever-receding ground that can be articulated ultimately only in relation to a non-representable abyss (Abgrund). A new topography of surface and writing emerges and replaces the surface/depth relationship. Both Hölderlin's poetics and Benjamin's criticism develop a model of representation based on a radical rethinking of writing and script, marked by a "cut" or "caesura" as the precondition of representation and of the possibility of any "thing" represented. In the recurring motif of waking up, Benjamin marks the threshold of that caesura and connects it at the same time with a specific trait of modern aesthetics as embodied in Kafka's work.
Keywords: Hölderlin; Walter Benjamin; poetic language; literary criticism; poetics; surface; depth; non-representable abyss; Abgrund; topography of surface; criticism; cut; caesura; thing; waking up; Kafka; modern; aesthetic